The risks of digital media: psychological changes in brazilian footballers - Morao, Kauan Galvao [UNESP]; Bagni, Guilherme [UNESP]; Verzani, Renato Henrique [UNESP]; Machado, Afonso Antonio [UNESP]; Fischer, Carlos Norberto [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2020)
Football and futsal have scenarios composed of numerous factors that can interfere in sports performance, including social media, which may have possible implications for footballers that use this kind of media. The objective of this study is to exhibit changes that can be provided by digital media in footballers, presenting possible emotional changes triggered in these athletes. The method used was qualitative and quantitative, with a descriptive nature. Data collection was performed by applying a closed questionnaire. The sample consisted of 59 university futebol and futsal athletes (24 female and 35 male), with a mean age of 23.43 years (+/- 4.57). It has been found that athletes use a variety of digital media, and most of them have already experienced a case of overexposure or cybercrime. In addition, the athletes asserted that these factors can negatively interfere in the most diverse relationships existing in these individuals' lives, as well as in sports performance, which can be a possible cause of abandonment of the sport. It was also found several emotional changes considered negative, arising from possible situations experienced by athletes, causing interference of various psychological factors level' and generating imbalance in footballers. It is suggested that athletes should be better oriented on the use of technological resources, to avoid, or at least minimize, cases of overexposure and the emergence of cybercrime, minimizing such harmful emotional changes and negative interference in sports performance such as personal life of these athletes.
Keywords: Emotions; Sport Psychology; Human Development; Social Media